Development and feasibility pilot study of positive psychological intervention for maintenance hemodialysis patients in China - Yang, Jie; Li, Yong-Qi; Gao, Xin-Yue; Cao, Yong-Hui; Chen, Jing; Liu, Ling-ling; Wang, Yi-Ru; Qian, Yue-Qin; Wu, Jing; Chu, Jing (Frontiers in Psychology, 2025)
BackgroundPsychological problems are prevalent among maintenance hemodialysis (MHD) patients, and development of scientific, feasible and effective psychological promotion strategies can effectively improve their mental health. A series of studies were conducted to develop a group-based positive psychological intervention for MHD patients. The feasibility and effectiveness of the protocol were verified by a study.MethodsA cross-sectional survey of 246, including interviews with 13 patients, was conducted to determine the status and factors influencing mental health. A scoping review of 65 studies was performed to develop a protocol for the group-based positive psychological intervention for MHD was based on the PERMA theory and lasted for 4 weeks. Furthermore, experts, medical workers and patients who completed the intervention were interviewed to refine the program. Fifty-two patients were recruited from a hemodialysis center in Shanghai from December 2023 to January 2024. The primary outcome was benefit finding (BF). The secondary outcomes were well-being, quality of life (QoL), and the accessibility and implementation of the program, which were evaluated through interviews and researcher logs.ResultsA total of 84 patients were recruited, 52 of whom ultimately participated in the study, including 26 patients in the intervention group and 26 patients in the control group. Twenty-four patients (92.31%) completed all interventions, and 26 patients (100%) completed more than 7 interventions. There were statistically significant differences in the intergroup effect (F = 4.603, p = 0.037 < 0.05), time effect (F = 5.663, p = 0.006 < 0.05) and interaction effect (F = 4.657, p = 0.015 < 0.05) of BF between the two groups. Moreover, through the intervention, the patients’ well-being and QoL in terms of the physical health dimension score improved.ConclusionThis study developed a group-based positive psychological intervention for MHD patients by conducting a scoping review, a cross-sectional study, qualitative interviews and expert group meetings. This study further optimized and verified the protocol of the intervention by analyzing the barriers to and facilitators of the intervention, conducting expert group meetings and performing the experiment. The intervention had a positive effect on physical and mental health for MHD patients.Clinical trial registrationBenefit Finding Promotion Program of Maintenance Hemodialysis Patients: An Empirical Study Based on the Implementation Science, identifier [https://www.chictr.org.cn/showproj.html?proj=209809, ChiCTR2300077469].